Refleksif dirinya: Satu analisis sintaksis - Dr. Fazal Mohamed Mohamed Sultan, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
This article discusses noun phrase (NP) diriya which is known as reflexive in Malay language. However, this reflexive has an ambiguous reading in a sentence. This is because the NP dirinya can have a reference in a clause as well as outside a clause in the same sentence. As a result, this reflexive disobeyed Principle A. On the other hand, this type of reflexive occasionally is known as a long distance reflexive. Mashudi and Solakhiah (1997) had analysed this form of dirinya in a generative framework. They have claimed that the ambiguous reading of this reflexive dirinya was caused by the existence of [+reflexive] and [+pronominal] features which is generated by the NP dirinya at Sstructure. Even though, both of these language experts have argued very convincingly that the reason for the ambiguity of the NP dirinya was because of the different of features that existed on the NP but they didn’t explain how two readings could have co-existed at the same level in the syntax. Their suggestions to have two readings to operate at the same level will not be able to reach the explanatory adequacy of a grammar. This analysis too will not be able to explain sentences like these: Sayai percaya bahawa Salimj telah menembak dirinya*i/j/k. (I believe that Salim has shot himself) atau Salimj percaya bahawa sayai telah menembak dirinya*i/j/k.( Salim believe that I have shot himself/myself). Therefore, this paper will try to fill the gaps. This analysis claims that the reasons for the ambiguity is due to the features [+3] and [+pronominal] on the enclitic ‘-nya’ and the feature [+reflexive] on the form diri which operates at a different syntactic level. This means that the ambiguity reading on dirinya in a sentence is because at the D-structure the native speaker will have the pronominal reading and it continues to exist until the Sstructure. At the S-structure, the speaker will have reflexive reading. The existence of two readings at different levels will cause dirinya to have an ambiguity reading. This analysis will be argued using the Binding Theory which controls the distribution of NP in a sentence